2019
DOI: 10.1016/j.molstruc.2019.01.080
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy of glycolic acid complexes with N2

Abstract: This is a self-archived version of an original article. This version may differ from the original in pagination and typographic details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…This indicates the presence of an additional unstable site. Similar conclusions were drawn for bands observed during the Raman spectroscopy study [16] of the GA/N 2 /Ar matrices (see Table 1).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…This indicates the presence of an additional unstable site. Similar conclusions were drawn for bands observed during the Raman spectroscopy study [16] of the GA/N 2 /Ar matrices (see Table 1).…”
Section: Resultssupporting
confidence: 87%
“…The first question to answer is whether both AAT and GAC complexes with N 2 are formed in the irradiated/annealed matrices. This question is particularly relevant in the context of the recently published results of the GA…N 2 complexes studied by Raman spectroscopy [16], which indicate that only the AAT…N 2 complex is present in argon matrices. The analysis of the νC=O region of the GA/N 2 /Ar matrices obtained upon irradiation at 1438, 1440, and 1442 nm (Figure S2 and Table S2 in Supporting Information) reveals that both AAT (1806 cm −1 ) and GAC (1784 cm −1 ) carbonyl stretching vibrations were disturbed by the presence of nitrogen, as shown by broadening/shift of the corresponding monomer νC=O bands.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these dimers were formed between SSC conformers: one dimer with hydrogen bonds between the two carboxylic OH groups, one structure with hydrogen bonds between the two alcoholic OH groups and a mixed structure with one OH group from the carboxylic group acting as proton donor and the alcoholic OH group on the other subunit acting as proton acceptor. Molecular complexes between GA and molecular nitrogen were identified in a study applying Raman spectroscopy for argon-trapped species upon high vibrational excitation experiments [22]. In that study, nitrogen was found to form complexes with two GA conformers (SSC and AAT) in low temperature argon environment.…”
Section: Introductionmentioning
confidence: 99%